Praktik Model Bisnis Berkelanjutan pada Komunitas UMKM di Yogyakarta - G Hendra Poerwanto; Kristia Kristia; Fransisca Desiana Pranatasari (EXERO : Journal of Research in Business and Economics, 2019)
Each business requires an effort to start thinking towards the sustainability of their business. Most businesses have a primary goal to take advantage, but now, they must turn to comprehensive thinking about other aspects beyond profit, namely people and planet. Profit, people and planet are often called tripple bottom line. Reinforcement the aspects of value proposition, value creation, and value capture, MSMEs in Indonesia will survive long-term. The study was conducted at the MSME community in Yogyakarta namely Pasar Kamisan, Pasar Moncer and Pasar Mustokoweni. We interview the main manager and community members. To support qualitative data, researchers conducted a survey to see the alignment of community missions with those of community members. As a result, members have felt that community managers have a strong commitment to support them in achieving a sustainable business model. However, in implementing this sustainable business model it is not easy. Various challenges faced by community managers as well as members.